Regulating competition in stock markets antitrust measures to promote fairness and transparency through investor protection and crisis prevention - Klein, Lawrence Robert; Dalko, Viktoria; Wang, Michael H. (Wiley, 2012)
A guide to curbing monopoly power in stock markets Engaging and informative, Regulating Competition in Stock Markets skillfully analyzes the impact of the recent global financial crisis on health and happiness, and uses this opportunity to put regulatory systems in perspective. Happiness is lost because of emotional and physical health deterioration resulting from the crisis. Therefore, the authors conclude that financial crisis prevention should be the focus of public policy. This book is the most comprehensive study so far on potential risks to the stock market, especially various forms of m.
Includes bibliographical references and index
Keywords: Stock exchanges -- State supervision; Stock exchanges -- Government policy; Financial crises; Competition; Bourse; Contrôle de l'État; Bourse; Politique gouvernementale; BUSINESS & ECONOMICS; Investments & Securities; General; Stock exchanges; Government policy; Stock exchanges; State supervision